2007
DOI: 10.1002/jlcr.1420
|View full text |Cite
|
Sign up to set email alerts
|

The Service Hospitalier Frédéric Joliot – contributions to PET chemistry over the years

Abstract: The Service Hospitalier Fré dé ric Joliot (SHFJ) (CEA-Orsay, France) has been a stimulating interdisciplinary research platform in medical imaging for almost half a century and particularly in the field of positron emission tomography (PET). In this context, PET chemistry, the driving force in molecular imaging, has occupied the front stage, especially where it concerns the short-lived radioisotopes carbon-11 and fluorine-18. In this review, important marks left by the SHFJ actors over the years will be highli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 201 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…Previously, it has been shown that rhodium-mediated reactions with 11 C]CO, forming ureas, are rapid and provide high yield [23-25]. Therefore, in the present, study 11 C]CO was used to synthesize 11 C]phenytoin by rhodium-mediated carbonylation with the aim of improving both specific activity and radiochemical yield of 11 C]phenytoin compared with an earlier method based on 11 C]COCl 2 [26], which resulted in low specific activity of the product following a rather tedious radiochemistry [26,27]. The purpose of the present study was to synthesize 11 C]phenytoin by carbonylation and to assess its characteristics as a P-gp substrate in rats in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…Previously, it has been shown that rhodium-mediated reactions with 11 C]CO, forming ureas, are rapid and provide high yield [23-25]. Therefore, in the present, study 11 C]CO was used to synthesize 11 C]phenytoin by rhodium-mediated carbonylation with the aim of improving both specific activity and radiochemical yield of 11 C]phenytoin compared with an earlier method based on 11 C]COCl 2 [26], which resulted in low specific activity of the product following a rather tedious radiochemistry [26,27]. The purpose of the present study was to synthesize 11 C]phenytoin by carbonylation and to assess its characteristics as a P-gp substrate in rats in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…The use of the methylation reagent [ 11 C]methyl triflate41–44 was privileged for the labeling at the 5‐methylpyridazino[4,5‐ b ]indole moiety (leading to compound 1a ), whereas [ 11 C]methyl iodide45 was preferred for the labeling at the N,N ‐dimethylacetamide function (leading to compound 1b ), a choice based on literature reports as well as on our own experience with similar structures 4, 25, 46. The nor ‐derivatives needed as precursors for labeling as well as SSR180575 itself needed as a reference were synthesized at Sanofi‐Aventis 47…”
Section: Resultsmentioning
confidence: 99%
“…The successful use of carbon‐11 in the labelling of an impressive variety of chemical structures is undoubtedly related to the exhaustive development of the so‐called secondary precursors . These labelled synthons, usually single‐carbon reactive molecules, are prepared from a primary precursor ([ 11 C]CO 2 or [ 11 C]CH 4 ), often by ‘on‐line’ or one‐pot procedures and are used as building blocks for the labelling of different chemical functions.…”
Section: Introductionmentioning
confidence: 99%